Use of OCT Angiography in Choroidal Melanocytic Tumors - Juan J. Toledo; Mónica Asencio-Duran; Jesús R. García-Martinez; Alejandro López-Gaona (Journal of Ophthalmology)
Objective. To describe OCTA findings in choroidal melanocytic tumors, especially the microcirculation patterns, and to try to correlate with the histopathological studies. Methods. Cross-sectional, comparative, observational study. 70 cases, including 55 choroidal nevi and 15 choroidal melanomas. Three different observers evaluated specific variables in the choriocapillaris layer on AOCT images and searched for images which described histopathologic vascular patterns, and also, a general description of the images was made. Complementary multi-imaging studies included EDI SD-OCT, color and autofluorescence fundus imaging, Doppler ultrasound, and indocyanine/fluorescein angiography. Main Results. Good quality studies were acquired in 80% of the cases, with kappa indexes 0.768–0.958. Nevus OCTA images were described mainly as hyperreflective (72.7%), whereas choroidal melanoma as iso/hyporeflective (62.5%). Avascular areas were found in 50.96% and in 33.3% of choroidal nevus and choroidal melanomas, respectively. A neovascular membrane was found only in cases of choroidal nevus (16.3%). Only in cases of choroidal melanomas, we found vascular loops (6.6%) or vascular networks (6.6%). Conclusion. OCTA is a promising new technology that can be used to study in vivo the differential characteristics of microcirculations between posterior segment melanocytic lesions. Today, larger studies are needed to corroborate these findings and to correlate it with malignancy.